2021
DOI: 10.1093/heapol/czab087
|View full text |Cite
|
Sign up to set email alerts
|

Geographic barriers to achieving universal health coverage: evidence from rural Madagascar

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 49 publications
(156 reference statements)
2
31
0
Order By: Relevance
“…These results suggest that suboptimal testing and treatment of malaria infections in these areas, due to geographic barriers to access health care [ 52 ], could result in undetected pockets of malaria transmission that undermine elimination goals. Indeed, previous studies have shown that persistent geographic inequalities in health care access still exist in rural areas of Madagascar, with an exponential decrease in the use of health facilities over the first 5 km [ 53 ]. Community health programs can be an effective way to remove geographic barriers to health care access [ 54 ], since two community health workers are present in every fokontany independently of their distance to a health facility.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that suboptimal testing and treatment of malaria infections in these areas, due to geographic barriers to access health care [ 52 ], could result in undetected pockets of malaria transmission that undermine elimination goals. Indeed, previous studies have shown that persistent geographic inequalities in health care access still exist in rural areas of Madagascar, with an exponential decrease in the use of health facilities over the first 5 km [ 53 ]. Community health programs can be an effective way to remove geographic barriers to health care access [ 54 ], since two community health workers are present in every fokontany independently of their distance to a health facility.…”
Section: Discussionmentioning
confidence: 99%
“…Access to healthcare is a multidimensional metric [75]; however, physical (or geographic) access is consistently described as one of the most critical components of access to healthcare globally [76,77]. The literature shows that lack of physical access remains a dominating factor in decreased utilization of healthcare services which, in turn, propagates negative health outcomes [77][78][79][80][81][82][83][84][85].…”
Section: Health Impactmentioning
confidence: 99%
“…These communities are systematically left out of the majority of health services [87] by the geographic bias of healthcare centers and corresponding transportation networks toward wealthier and more populous urban centers [83,88,89]. Subsequently, in large part due to transportation-based issues, many people in rural and impoverished communities simply go without healthcare services [90], and therefore, face immense health challenges [76,86,91]. However, previous reviews of existing evidence have found positive correlations when investigating the impacts of rural road improvement upon healthcare access in rural communities [8,9].…”
Section: Health Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative is the use of geographic information from routine health system data. While PHCs typically keep records of a patient's residence to the lowest administrative level (9), this information is not systematically recorded in CHW registries.…”
Section: Introductionmentioning
confidence: 99%